2023
DOI: 10.1111/tpj.16385
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of chromatin configuration at AGAMOUS locus by LFR‐SYD‐containing complex is critical for reproductive organ development in Arabidopsis

Abstract: SUMMARYSwitch defective/sucrose non‐fermentable (SWI/SNF) chromatin remodeling complexes are evolutionarily conserved, multi‐subunit machinery that play vital roles in the regulation of gene expression by controlling nucleosome positioning and occupancy. However, little is known about the subunit composition of SPLAYED (SYD)‐containing SWI/SNF complexes in plants. Here, we show that the Arabidopsis thaliana Leaf and Flower Related (LFR) is a subunit of SYD‐containing SWI/SNF complexes. LFR interacts directly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Early work rapidly established that regulation of ABC genes expression is a multi-layered process integrating inputs from hormonal signaling pathways with the activity of transcription factors, histone modifying enzymes, and chromatin remodeling complexes and roles for post-transcriptional mechanisms often involving mobiles noncoding RNAs and RNA processing factors (e.g. Cheng et al 2003 ; Chen 2004 ; Zhao et al 2007 ; Yamaguchi et al 2009 ; Wu et al 2012 , 2018 ; Jung et al 2014 ; Sacharowski et al 2015 ; Poyatos-Pertíñez 2016 ; Morel et al 2017 ; Lee et al 2022 ; Lin et al 2023 ). These investigations exposed a 3-step waltz regulating ABC genes: upstream factors initiate transcription across broad territories (step 1), followed by refinement (step 2), and then maintenance (step 3) of precise expression domains.…”
Section: Swimming Upstreammentioning
confidence: 99%
“…Early work rapidly established that regulation of ABC genes expression is a multi-layered process integrating inputs from hormonal signaling pathways with the activity of transcription factors, histone modifying enzymes, and chromatin remodeling complexes and roles for post-transcriptional mechanisms often involving mobiles noncoding RNAs and RNA processing factors (e.g. Cheng et al 2003 ; Chen 2004 ; Zhao et al 2007 ; Yamaguchi et al 2009 ; Wu et al 2012 , 2018 ; Jung et al 2014 ; Sacharowski et al 2015 ; Poyatos-Pertíñez 2016 ; Morel et al 2017 ; Lee et al 2022 ; Lin et al 2023 ). These investigations exposed a 3-step waltz regulating ABC genes: upstream factors initiate transcription across broad territories (step 1), followed by refinement (step 2), and then maintenance (step 3) of precise expression domains.…”
Section: Swimming Upstreammentioning
confidence: 99%
“…An additional factor for AG activation was recently described: LEAF AND FLOWER-RELATED (LFR) is a subunit of the SAS complex and functions interdependently with SYD to activate AG expression ( Lin et al., 2023 ). LFR is an Armadillo-repeat-containing nuclear protein with known roles in leaf development through its interactions with various components of the SWI2/SNF2 chromatin complex, such as SWI3B and SWIP37B ( Vercruyssen et al., 2014 ; Nelissen et al., 2015 ; Lin et al., 2018 ; Lin et al., 2021 ).…”
Section: Floral Meristem Development In 4d: Spatiotemporally Resolved...mentioning
confidence: 99%
“…The genetic association between SWI/SNF components and flower development-related transcription factors was established over two decades ago when the syd mutation was found to enhance the floral homeotic defects in the weak lfy mutant (Wagner and Meyerowitz, 2002;Bieluszewski et al, 2023). In brm and syd, the expression of several floral homeotic genes is downregulated (Hurtado et al, 2006;Wu et al, 2012;Lin et al, 2023). It has been reported that LFY and the MADS-box transcription factor SEP3 recruit BRM and SYD to counteract Polycomb repression at the floral homeotic genes AP3 and AGAMOUS (AG) during flower development (Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the AP-MS results have demonstrated that BRM, SYD, and certain other SWI/SNF subunits are co-purified with multiple MADS transcription factors in flowers (Smaczniak et al, 2012), indicating interactions between SWI/SNF components and MADS transcription factors involved in flower development. A recent report has shown that LEAF AND FLOWER RELATED (LFR), a shared subunit of SAS and MAS, collaborates with the SAS catalytic subunit SYD to regulate the chromatin state and transcription of AG (Lin et al, 2023). These studies have mainly focused on the regulation of SWI/SNF components on specific genes associated with flower development.…”
Section: Introductionmentioning
confidence: 99%